2018
DOI: 10.1371/journal.pone.0194202
|View full text |Cite
|
Sign up to set email alerts
|

Reduced inflammation and cytokine production in NKLAM deficient mice during Streptococcus pneumoniae infection

Abstract: Streptococcus pneumoniae is a leading cause of pneumonia and a significant economic burden. Antibiotic-resistant S. pneumoniae has become more prevalent in recent years and many pneumonia cases are caused by S. pneumoniae that is resistant to at least one antibiotic. The ubiquitin ligase natural killer lytic-associated molecule (NKLAM/RNF19b) plays a role in innate immunity and studies using NKLAM-knockout (NKLAM-KO) macrophages have demonstrated that NKLAM positively affects the transcriptional activity of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Recent studies from our laboratory demonstrated that STAT1 tyrosine phosphorylation is lower in NKLAM -/- than in WT mice upon bacterial infection [7]. We found that infection with SeV induced the phosphorylation of tyrosine 701 in STAT1 in the lungs of both WT and NKLAM -/- mice beginning at day 3 post-infection.…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…Recent studies from our laboratory demonstrated that STAT1 tyrosine phosphorylation is lower in NKLAM -/- than in WT mice upon bacterial infection [7]. We found that infection with SeV induced the phosphorylation of tyrosine 701 in STAT1 in the lungs of both WT and NKLAM -/- mice beginning at day 3 post-infection.…”
Section: Resultsmentioning
confidence: 47%
“…NKLAM has been localized to NK cell cytolytic granules [6] and macrophage phagosomes [5]. Additionally, we demonstrated that bone-marrow-derived macrophages (BMDM) and neutrophils from NKLAM-deficient mice have a significantly defective bactericidal response [5, 7]. These studies strengthen the role of NKLAM as an important component of the innate immune response.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…As such, bacterial pneumonia remains a significant public health concern (6)(7)(8). Although bacterial infection alone can initiate lung injury, it is the host-defense response that results in exaggerated inflammation and results in further lung injury and delayed recovery (9)(10)(11). Therefore, an improved understanding of the mechanisms underlying the host/pathogen interactions in bacterial pneumonia is imperative to develop new therapeutic strategies that balance the need for an adequate host defense with an injurious inflammatory response.…”
mentioning
confidence: 99%